2016
DOI: 10.2337/dc16-0430
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HbA1c and BMI on Lipid Trajectories in Youths and Young Adults With Type 1 Diabetes

Abstract: OBJECTIVETo assess the influence of HbA1c and BMI (measured as BMI z score [zBMI]) on LDL, HDL, and non-HDL trajectories as youths with type 1 diabetes age into early adulthood.RESEARCH DESIGN AND METHODSDynamic, retrospective cohort study examining changes in lipid values in 572 youths with type 1 diabetes followed longitudinally for a median of 9.3 years. Through longitudinal modeling, we describe the relationship of HbA1c and zBMI on lipid values as subjects age after adjusting for other relevant factors, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Poor glycemic control was associated with high non-HDL and total cholesterol among 682 children with T1DM seen at Barbara Davis Center for Childhood Diabetes [ 39 ]. In another retrospective cohort study of 572 youths with T1DM followed longitudinally for a median of 9.3 years, HbA1c modestly affected LDL-C and non-HDL cholesterol [ 40 ].…”
Section: Risk Factors For Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Poor glycemic control was associated with high non-HDL and total cholesterol among 682 children with T1DM seen at Barbara Davis Center for Childhood Diabetes [ 39 ]. In another retrospective cohort study of 572 youths with T1DM followed longitudinally for a median of 9.3 years, HbA1c modestly affected LDL-C and non-HDL cholesterol [ 40 ].…”
Section: Risk Factors For Cardiovascular Diseasementioning
confidence: 99%
“…Obesity is associated with atherogenic lipoproteins in youth with T1DM, which increases their CVD risk [ 39 , 50 , 51 ], and BMI is associated with worsening LDL-C over time [ 40 ]. In the SEARCH CVD study, 298 youths with T1DM and an average age of 13.3 ± 2.9 years, who had two study visits 5 years apart, BMI was the only modifiable risk factor that predicted CIMT based on a linear regression model [ 52 ].…”
Section: Risk Factors For Cardiovascular Diseasementioning
confidence: 99%
“…Earlier studies have attributed the dyslipidemia in type 1 diabetes to increased weight gain and worsening of glycemic control[ 12 , 18 ], but a detailed characterization of early-phase dyslipidemia of type 1 diabetes based on stratification of patients by PCR history has not been previously done. Such an investigation would clarify the possible role of non-remission as a non-modifiable risk factor for dyslipidemia in type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Included were all children and adolescents with proven T1D until the age of 25.0 years. Excluded were 472 patients (39.8 %), of which 420 (89.0 %) were excluded for not having at least two LDL values [7,12], and 43 (9.1 %) for having celiac disease. Patients receiving lipid-lowering medication at the start of this longitudinal study as well as patients starting this medication in the course of the study, were excluded.…”
Section: Study Design; Patient Selectionmentioning
confidence: 99%
“…In addition, this study and the studies of Reh and Edge showed patients to change lipid trajectories frequently and showed also that a considerable number of patients changed from low-risk or borderline-high-risk levels to more unfavourable lipid levels (los-ing track of lipids) [7][8][9]. This losing track of lipids is especially seen in patients with an increased glycated hemoglobin (HbA1c), longer diabetes duration, female gender and an increased body mass index (BMI) [7][8][9][10][11][12]. A diagnostic algorithm, such as suggested by Schwab [13], includes most of these determinants and was used by Schwab to develop group-specific reference curves for the several lipid parameters for children and adolescents with T1D [13].…”
Section: Introductionmentioning
confidence: 99%